2006
DOI: 10.1002/mame.200600150
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamic Mechanical Properties of Melt Intercalated Polyamide 6—Montmorillonite Nanocomposites

Abstract: Summary: Polymer‐layered silicate nanocomposites (PLSN), based on polyamide 6 (PA6) and montmorillonite (MMT) modified with an octadecylammonium salt, were produced via melt compounding in a co‐rotating twin‐screw extruder. Wide angle X‐ray diffraction (WAXD) and TEM revealed a PLSN containing 3.3% by weight (wt.‐%) of MMT to exhibit a mixed exfoliated/intercalated morphology, consisting mainly of individual silicate lamellae together with some intercalated stacks, resulting in a mean value of 1.8 lamellae per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
2
33
2
Order By: Relevance
“…It is also worth noting that the results obtained with PEBA/NaMMT are even better than the ones reported in the literature for PA6 filled with OMMT. Indeed, at 5 wt% clay loading, the normalized E% is 1.33 [2] or 1.34 [64] while it has been found to be 1.44 in the present study. Figure 10b shows the glass transition temperature (T g ) of the PEBA matrix versus mineral content, which corresponds to PA12 blocks.…”
Section: Analysis Of Peba/clay Nanocomposites Propertiescontrasting
confidence: 58%
“…It is also worth noting that the results obtained with PEBA/NaMMT are even better than the ones reported in the literature for PA6 filled with OMMT. Indeed, at 5 wt% clay loading, the normalized E% is 1.33 [2] or 1.34 [64] while it has been found to be 1.44 in the present study. Figure 10b shows the glass transition temperature (T g ) of the PEBA matrix versus mineral content, which corresponds to PA12 blocks.…”
Section: Analysis Of Peba/clay Nanocomposites Propertiescontrasting
confidence: 58%
“…The XRD data for these PLSN reported previously [11] did indicate that a more ordered, intercalated structure had developed in the PLSN as the MMT content was raised from 3.3 to 7.2 wt%. In addition, measurements of particle dimensions from TEM images [11] showed that the 5T PLSN exhibited a mean value of 1.8 silicate lamellae per particle, resulting from a particle distribution comprising a predominance of exfoliated lamellae together with a minority of intercalated lamella stacks containing between 2 and 6 lamellae. In contrast, the 10T PLSN exhibited a mean value of 3.8 silicate lamellae per particle [11], resulting from a particle distribution comprising a predominance of intercalated lamella stacks containing between 2 and 10 lamellae.…”
Section: Mechanical Testingmentioning
confidence: 51%
“…Thus, above a critical loading of MMT, proposed to be ≤ 5 wt% for MMT lamellae with aspect ratios of ≥ 100 [7], these constraints are predicted to result in the formation of an ordered nematic phase [16]. The XRD data for these PLSN reported previously [11] did indicate that a more ordered, intercalated structure had developed in the PLSN as the MMT content was raised from 3.3 to 7.2 wt%. In addition, measurements of particle dimensions from TEM images [11] showed that the 5T PLSN exhibited a mean value of 1.8 silicate lamellae per particle, resulting from a particle distribution comprising a predominance of exfoliated lamellae together with a minority of intercalated lamella stacks containing between 2 and 6 lamellae.…”
Section: Mechanical Testingmentioning
confidence: 76%
See 2 more Smart Citations